Developing English Materials for Nursing Students through Students' Need Analysis - Kristian Burhan; Hendra Putra (Journal of English Education and Teaching, 2021)
The study aims to find out the nursing students of AKPER YPTK Solok need in developing English materials. This research is classified as mixed method research design; qualitative research and survey research. In this research, there are two instruments; questionnaire and interview guidelines. The questionnaire aims to gain and collect information from students related to English teaching and learning. Interview guideline is used to gather information from English lecturer at AKPER YPTK Solok. The results of this research show that; (1) there are some skills and English components that are needed by the nursing students of AKPER YPTK Solok, they are; speaking skill, reading skill, vocabulary mastery, and grammar mastery. (2) This research also found that nursing students of AKPER YPTK Solok want English materials, including grammar and vocabulary related to nursing field to be more focused in teaching and learning process. Based on the results, it can be concluded that in developing English materials for nursing students, the lecturers and decision maker should know what the students and work field need through students; need analysis.